Blogosfera, estratégias de subversão e o campo da comunicação no Brasil: uma análise do Movimento dos Blogueiros Progressistas sob uma perspectiva de estudos organizacionais - Darbilly, Leonardo Vasconcelos Cavalier (2014)
The field of communication has undergone a process of intensive changes with respect to how news are produced, distributed and consumed. This phenomenon is linked mainly to changes in technology that have enabled new alternatives to produce and commercialize news that are different from the traditional model established by dominant organizations in this space. The Internet made possible that different civil society groups could express themselves more freely. In this sense, thanks to the use of new technologies of information and communication by such groups, a number of political blogs were created within the field whith the main purpose of challenging the power of traditional media and allowing the dissemination of political views different from those of mainstream organizations This new space is considered in this work as an alternative political blogosphere. Among the various groups of agents that entered the field of communication in recent times, it is possible to mention a specific organized movement that has gained visibility in recent years as much for its political activism as for its engagement in the discussion of media democratization in Brazil: The Movement of Progressive Bloggers (BlogProg). The BlogProg movement, which is composed by former journalists from major traditional media organizations, journalists working for alternative media vehicles, political activists and political parties linked to the left, was responsible for conducting several national meetings in order to discuss the formulation of public policies that guarantee the democratization of the field of communication in Brazil and that could encourage the brazilian blogosphere. In this sense, this thesis aims to analyze how the appeareance and consolidation of a Brazilian political alternative blogosphere made possible, especially since the creation of the movement, the emergence of strategies of subversion by different agents belonging to the field of communication in Brazil. In this thesis the author establishes a link between sociological theory of social fields developed by French sociologist Pierre Bourdieu and media activism perspectives, especially that developed by authors such as Carroll and Hackett (2006 ) and Hackett (2008). Data were collected through three techniques: First, partipant observation in major events sponsored by agents linked to the BlogProg movement. Second, online observation of thirteen blogs produced by bloggers identified with the movement. Finally, eighteen people were interviewed, among bloggers and digital activists who have some kind of relationship with the movement. It was possible to find that this new social movement makes use of different micro and macro strategies of subversion not only to challenge dominant organizations linked to traditional media, but also to change dominant rules and traditional order established within the field of communication.